The mechanical behavior of metal-halide perovskites: Elasticity, plasticity, fracture, and creep. (15th January 2023) - Dai, Zhenghong; Doyle, Meaghan C.; Liu, Xing; Hu, Mingyu; Wang, Qizhong; Athanasiou, Christos E.; Liu, Yucheng; Sheldon, Brian W.; Gao, Huajian; Liu, Shengzhong (Frank); Padture, Nitin P.
Abstract: Wide ranging mechanical properties — elasticity, plasticity, fracture, and creep — most relevant to the mechanical reliability of perovskite solar cells (PSCs) are systematically investigated. High quality bulk single-crystals of the commonly studied metal-halide perovskites (MHPs) relevant to PSCs are fabricated and studied: CH3 NH3 PbBr3 (MAPbBr3 ) and CH3 NH3 PbI3 (MAPbI3 ). The first direct measurement of MHP Young's modulus ( E ) using uniaxial compression reveals E <100> of 13.1 ± 1.3 and 10.6 ± 1.0 GPa for MAPbBr3 and MAPbI3, respectively. The Vickers micro-hardness H (100) of MAPbBr3 and MAPbI3 is 0.54 ± 0.02 GPa and 0.76 ± 0.05 GPa, respectively. The Vickers micro-indentation fracture toughness K IC of MAPbBr3 and MAPbI3 is estimated at 0.20 ± 0.03 MPa⋅m 0.5 and 0.18 ± 0.03 MPa⋅m 0.5, respectively. The stress-exponent, n, extracted from nanoindentation creep data is ∼8 and ∼10 for MAPbBr3 and MAPbI3, respectively. The trends in these properties are discussed. These properties are best estimates and are recommended for use in future mechanical behavior and reliability analyses of MHPs and PSCs. Graphical abstract: Image, graphical abstract